2019
DOI: 10.1016/j.measurement.2018.12.080
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the energy efficiency estimation methods on induction motors considering real-time monitoring

Abstract: Different methods have been developed to estimate the energy efficiency of induction motors. The accuracy of these methods vary with the load factor, the unbalanced voltage (UV) and harmonics. The feasibility of these methods for efficiency estimation in real-time were theoretically and experimentally assessed during the operation under different operational conditions (i.e. balanced sinusoidal voltage (BSV), harmonics, UV and harmonics with UV). Results show that for load factors over 80%, the air-gap method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Induction motors account for around half of all global electric power use. They are built and designed for practical simplicity, unlike any other electrical counterparts; permanent magnets are unneeded, mostly are brushless, and have no commutator rings or position sensors [1]. Induction motors are also capable of self-starting operations.…”
Section: Introductionmentioning
confidence: 99%
“…Induction motors account for around half of all global electric power use. They are built and designed for practical simplicity, unlike any other electrical counterparts; permanent magnets are unneeded, mostly are brushless, and have no commutator rings or position sensors [1]. Induction motors are also capable of self-starting operations.…”
Section: Introductionmentioning
confidence: 99%
“…The three-phase asynchronous motors (TAM) are one of the most important loads in EPS since it is estimated that there are around 300 million of this equipment installed in industries [4], representing the consumption of around 43 to 46% of energy electricity worldwide and between 60 and 70% of energy in industries [5]- [7]. Due to the importance of TAMs, they have been the subject of numerous studies focused mainly on the improvement of the technology to increase the level of efficiency [8], [9], on control strategies in the TAMs drive system to guarantee maximum operating efficiency [10]- [12] and on methods for estimating TAM operational efficiency [13], [14] The importance of improving the modeling of TAMs in the simulation programs of EPS was evidenced by the blackout in the United States that occurred in 1996 and 2000 when millions of North Americans were without electricity for several hours [15]. In a study led by the "western electricity coordinating council," it was shown that the system in the affected area did not include the modeling of various TAMs and electronic loads, therefore, the behavior of the EPS could not be predicted correctly [16]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…Induction motors (IMs) account for some 68% of the energy consumption of industry worldwide; thus, to reduce the global consumption of electricity, it is essential to improve their efficiency. Furthermore, improving the efficiency of IM and drive mechanical systems might reduce around 20%-30% of the energy consumption, also reducing some 10% of the overall electricity demand [2]. IM has one disadvantage, the fact that the mechanical speed of the machine is directly coupled to the frequency of the supply voltage, which limits its flexibility when supplied directly from the grid.…”
Section: Introductionmentioning
confidence: 99%